Pharmacological rescue in patient iPSC and mouse models with a rare DISC1 mutation - Nam-Shik Kim (Nature Portfolio, 2021)
Previous work has shown in iPSC derived neurons that synaptic impairments are associated with a 4bp DISC1 deletion. Here the authors demonstrate a role for the PDE4 signalling pathway in these synaptic impairments.